Fringe Benefits Among US Orthopedic Residency Programs Vary Considerably: A National Survey. Issue 2 (July 2016) - Clement, R. Carter; Olsson, Erik; Katti, Prateek; Esther, Robert J.
Background: Residency programs compete to attract applicants based on numerous factors. Previous research has suggested that medical students consider quality of life among the most important factors in selecting a program. One aspect of workplace quality of life is the cadre of non-monetary benefits offered to employees. However, with federal funding for graduate medical education (GME) under consideration for spending cuts, the source and continuation of such benefits may be in question. Questions/Purposes: This study aimed to determine the level and variability of benefits beyond standard salary and insurance options available to trainees at US orthopedic residency programs and to assess the source of funding for those benefits. Methods: A 26-question survey investigating various benefits and funding sources was circulated by email to all ACGME-accredited orthopedic residency programs. Results: The survey was sent to 153 programs and 69 responded (45%). The majority offers their residents discretionary funds (77%) and conference funding (96%), most of which comes from the department, followed by the hospital or GME funding. Forty-one percent of respondents permit their residents to moonlight. The majority of respondents provide meal stipends (93%), free parking (71%), gym benefits (63%), surgical loupes (53%), and maternity/paternity leave beyond vacation time (55%). No statistically significant differences were found among top ranked residencies, top ranked orthopedic hospitals, or academic centers compared to their counterparts. Conclusion: While some benefits are commonly offered, there is great variation in the availability and level of others. However, these differences were independent of program and hospital reputation as well as academic center status. Departments currently bear a substantial amount of the cost of these benefits internally.